2018
DOI: 10.1093/brain/awy002
|View full text |Cite
|
Sign up to set email alerts
|

Beyond the face: how context modulates emotion processing in frontotemporal dementia subtypes

Abstract: The importance of assessing social cognition to characterize dementia syndromes is increasingly recognized, with lower social cognition capacity associated with reduced functional independence and greater carer burden. Emotion recognition is impaired in both behavioural-variant frontotemporal dementia and semantic dementia, yet the social and behavioural changes observed in these syndromes in everyday situations varies. To date, most studies have investigated isolated, context-free stimuli indexing recognition… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
54
0
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 79 publications
(64 citation statements)
references
References 67 publications
8
54
0
2
Order By: Relevance
“…Studies, which are carried out by magnetic functional resonance (fMRI), have demonstrated that body emotional posture influence in facial expression processing (Poyo-Solanas et al, 2018). Moreover, it has been suggested that the regions that are in charge of processing dynamic body movements are linked to emotional and body recognition (Kumfor et al, 2018). Using tasks of the same kind of our study, emotional recognition patterns in context in teenagers with criminal conduct have been explored (Santamaría-García et al, 2019), and with patients who suffer from frontotemporal dementia (Kumfor et al, 2018).…”
Section: Emotional Recognition: Hypothesis Of Physical Exercise As a mentioning
confidence: 91%
See 2 more Smart Citations
“…Studies, which are carried out by magnetic functional resonance (fMRI), have demonstrated that body emotional posture influence in facial expression processing (Poyo-Solanas et al, 2018). Moreover, it has been suggested that the regions that are in charge of processing dynamic body movements are linked to emotional and body recognition (Kumfor et al, 2018). Using tasks of the same kind of our study, emotional recognition patterns in context in teenagers with criminal conduct have been explored (Santamaría-García et al, 2019), and with patients who suffer from frontotemporal dementia (Kumfor et al, 2018).…”
Section: Emotional Recognition: Hypothesis Of Physical Exercise As a mentioning
confidence: 91%
“…In that way, understanding how environmental factors, such as PE, contribute to the performance of emotional recognition in context, and in ecological situations, is a novel area that answers to current questionings of social and cognitive neuroscience (Aviezer et al, 2008;Kumfor et al, 2018). We assumed that acute PE has positive effects on emotional recognition.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Structural and functional abnormalities of the cerebellum are present in numerous developmental and acquired neurological conditions, such as developmental dyslexia, autism spectrum disorders, alcohol‐related brain damage, movement disorders (eg, Friedreich ataxia, Parkinson disease, Huntington disease), dementia (eg, Alzheimer disease [AD], dementia with Lewy bodies, frontotemporal dementia), and psychiatric disorders . The contribution of the cerebellum to motor coordination and motor planning is well known, but many studies have downplayed its involvement in other domains despite the mounting evidence over the past 30 years (eg, language, social cognition, interoception).…”
mentioning
confidence: 99%
“…Despite the robust size of this pathology-proven cohort, future studies including more subjects are warranted. Moreover, this retrospective, path confirmed study includes relatively old cases, so the neuropsychological data available do not include more recent measures such as Famous Faces Naming or Emotion Processing tasks (Kumfor et al, 2018). Larger samples, including the more targeted neuropsychological tests now available, will allow more refined investigation of the neural correlates of specific phenotypical characteristics of TDP-43-C driven temporal FTDs.…”
Section: Discussionmentioning
confidence: 99%